Kumulatives Walzplattieren : Bewertung der Umformeigenschaften mehrlagiger Blechwerkstoffe der ausscheidungshärtbaren Legierung AA6014 - Herrmann, Jürgen (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Accumulative Roll Bonding is a well-known process for the production of semi-finished sheet material with an ultra-fine grained microstructure. Against the background of lightweight design, the increase in strength that can be achieved is a significant advantage. The industrial implementation of the process is prevented by a lack of knowledge of the material behavior of the high-strength, multi-layered sheet material in forming processes. The aim of this work is the evaluation of the forming properties of the ultra-fine grained aluminum alloy AA6014. For this purpose, the resulting material properties are examined depending on the parameters of the Accumulative Roll Bonding process. The focus is on a new approach to tempering the working rolls in the rolling process. The forming properties as well as the forming limits are analyzed based on the processes of deep drawing and bending. Finally, the well-known approach of Tailor Heat Treated Blanks technology to enhance the formability as a result of a local short-term heat treatment is transferred to the multi-layered, high-strength aluminum alloy AA6014. On the basis of the results of this work, the performance of the investigated materials for use in metal forming technology is demonstrated. Increasing the potential for lightweight construction by significantly increasing the specific strength of semi-finished sheet material can make a contribution to meeting the high requirements for future mobility concept